2014
DOI: 10.1063/1.4861656
|View full text |Cite
|
Sign up to set email alerts
|

Generation and control of spin-polarized photocurrents in GaMnAs heterostructures

Abstract: Articles you may be interested inQuantum-level control in a III-V-based ferromagnetic-semiconductor heterostructure with a GaMnAs quantum well and double barriers Appl. Phys. Lett. 96, 052505 (2010);

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recent research has indicated that the generated photocurrents could also be spin-polarised. The application of a relatively small static field can affect the spin-polarisation for some photon energies (Bezerra et al, 2014). Further investigation of these effects is required.…”
Section: Humidity Effect or Static Electric Field Effectmentioning
confidence: 99%
“…Recent research has indicated that the generated photocurrents could also be spin-polarised. The application of a relatively small static field can affect the spin-polarisation for some photon energies (Bezerra et al, 2014). Further investigation of these effects is required.…”
Section: Humidity Effect or Static Electric Field Effectmentioning
confidence: 99%
“…Because of the conservation of angular momentum, the circular dichroism can also be reflected by the polarization direction and the magnitude difference between the spin polarization carriers excited by left and right circularly polarized light. A further way to study magnetic properties of (Ga,Mn)As is to investigate the spin-polarized current or conductance9. Recently, spin-polarized photocurrents in DMS systems subjected to an external magnetic field induced by microwave or terahertz radiation have been observed, which is attributed to the giant Zeeman spin splitting or the spin-dependent carrier scattering10.…”
mentioning
confidence: 99%
“…Recently, spin-polarized photocurrents in DMS systems subjected to an external magnetic field induced by microwave or terahertz radiation have been observed, which is attributed to the giant Zeeman spin splitting or the spin-dependent carrier scattering10. So far almost all of the magnetic measurements, no matter the magnetic circular dichroism(MCD)111213 or the spin-related current910, need an external magnetic field, which causes the Zeeman splitting inevitably and may make the results conflicting.…”
mentioning
confidence: 99%